FACTORS RELATED TO MOTHER COMPLIANCE CARRYING OUT COMPLETE PRIMARY IMMUNIZATION IN THE WORK AREA OF CIHIDEUNG COMMUNITY HEALTH CENTER TASIKMALAYA CITY - Tatu Septiani Nurhikmah; Kusnandi Rusmil; Elsa Puji Setiawati (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Immunization must be given to all babies in Indonesia. However, the complete primary immunization was still unsuccessful because of the mother’s compliance to immunizing her baby. The study goal was analyzing pertain factor of mother’s compliance in applying complete primary immunization. The study design applies a mixed-method completed by a sequential exploration strategy. The first stage was a quantitative method to 70 mothers that have a baby age of 12-13 months by using simple random sampling; measuring instrument was a questionnaire, then the data analyzed by chi-square and double logistic regression. The second stage was a qualitative method to 10 mothers by applying purposive sampling, guided by in-depth interviews. The study result of the quantitative bivariable analysis method shows knowledge, attitude, motivation, and family support correlate with the mother’s obedience in doing complete primary immunization (p-value 0,001). Multivariable analysis results the dominant affected factor is knowledge (p-value 0,001) with OR 62,21, while motivation with (p-value 0,007) OR 31,98. Furthermore, the qualitative analysis result shows the mother’s assumption that the healthy baby did not need to be immunized, she did not know that their baby has not immunized yet, the incomplete immunization information, fever worried, lazy, and believe. Vaccine limitation becomes some factors that interfere with complete primary immunization. Thus, the dominant factor of the mother’s obedience is knowledge and motivation. Keywords: Immunization, mother, obedience